(untitled) (Chittagong University Journal of Biological Sciences, 2024)
The Halda River, one of the major natural spawning areas for Indian Major Carps (IMCs), is in danger due to some infrastructure development. This research identified 22 biologically important deeper areas or Kums (locally called) of the river that harbours more fish than other areas. The study was initially started in 2019, and with the follow-up study in 2022 and 2023, the reduction in 17 and 18 Kum’s depth was determined respectively. The study also found a significant reduction in fish numbers at a 5% level of significance, stating that, if the depth of Kum decreases by 1 meter, about 3 fish will be lost per 10000 m2. The reduction of Kum’s depth most affects fish between 85 and 100 cm long. The study identified 8 significant reasons for the destruction of Kums, among which geobags and cemented blocks were the deadliest ones. Chittagong Univ. J. B. Sci. Vol. 12 (1 & 2): 103-114, 2024